The difficult airway : a practical guide - Hagberg, Carin A.; Artime, Carlos A.; Daily, William H. (New York : Oxford University Press, 2013)
This guide provides practical guidelines for improving the success rates of airway managers of all specialties who use modern airway devices and techniques. The book addresses various clinical scenarios in a user-friendly format that mimics the approach clinicians encounter at educational workshops.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Airway (Medicine); Respiratory therapy; Respiratory organs -- Obstructions